Komunikasi Persuasif Band Crashead Pada Isu Sosial Di Acara Hardcore Everyday - Awaludin, Rizal; Astuti Itasari, Andri (Solidaritas, 2025)
One of the bands that speaks about social issues is Crashead, a band from Surakarta. Crashead is a band that has a Hardcore music genre whose songs convey messages related to social issues in their work. The purpose of this study was to determine how the Crashead band's persuasive communication on social issues at the Hardcore Everyday event. This study uses descriptive qualitative with information processing theory according to Mcguire. The informants of this study were Crashead personnel, and students who like Hardcore music and follow the Crashead band. The sampling technique used purposive sampling technique. Data collection was carried out by interviews, observation and documentation. The results of the study showed that there was a persuasive communication process or influence in the music of the Crashead band towards the audience, namely students. The Crashead band's persuasive communication process conveys persuasive messages in the form of social issues, and the audience, namely students, paysattention to the social issue message, after that students will understand the social issue message, they will be influenced and believe the arguments of the social issue message conveyed, then there will be a new adoption position for students, and finally there is a change in student behavior desired by the Crashead band. The persuasive process occurs verbally and nonverbally to students. The Crashead band conveys its thoughts on social issues verbally through underground concerts and one of them is Hardcore Everyday as a forum for them to change the behaviorof their audience regarding social issues that are happening around us. In addition, nonverbal delivery with music listeners who listen through digital streaming platforms and through social media from the Crashead band.